PENDEKATAN FENOMENOLOGI DALAM KAJIAN AGAMA - Ridlwan, Nurma Ali (Fakultas Dakwah IAIN Purwokerto, 2013)
The scientific study of religion can be traced to the 19th century and theearly of 20th century, which was influenced by rennaissance. The objectives ofscientific religion was to give an objective description, especially to the westernpeople, of various aspects of religious life in this world. Most of the made somecomparition and demonstrated the superiority of western culture and religioncompared with those of other parts of the world.Moders scientist insist on taking their approaches and disciplines from premodernstudies which contained subjective and normative assumptions andperspectives, depended on supranatural and other authority, and ignored thestandards of accurate and objective science.In relation to the above condition, phenomenology of religion emerged asan effort to avoid etnocentrical and normative approaches.